PENGENDALI SUHU DAN KELEMBABAN PADA TANAMAN SELADA (Lactuca sativa L) DENGAN SISTEM AEROPONIK BERBASIS ARDUINO UNO R3 - Sariayu, Martha Vira; supriono, supriono (Faculty of Engineering, Universitas Tanjungpura, 2017)
Lettuce cultivation (Lactuca sativa L.) in Indonesia until now still using the method of planting in open land that has many obstacles and requires a large enough land. The impact is the disruption of crop growth that affects the productivity and availability of land required. To overcome it can be applied a method of aeroponic cultivation of plants with a vertical system that avoids plants from pests and can save places for planting. Cultivation of plants with aeroponic system makes it easier for us to control the variables needed by lettuce plants such as temperature and humidity. The aim of this reasearch is to design the air and humidity control system in aeroponic media in the range needed by the lettuce plant, that is at a temperature of 25 oC to 28 oC and humidity in the range of 65% to 78%. For the measurement of ambient temperature and humidity of the environment can be selected sensor DHT11. DHT11 has a calibrated digital output, connected directly to the Atmega32P microcontroller in board Arduino Uno R3, and the driver as a switch for the pump and fan.When temperature >28oC then the pump will be turn on and when the humidity>79% then the fan will turn on, control systems work on-off. From the two media tested that is media A (with the controller) and media B (without the controller), Lettuce plants in media A grow with an average plant height increase of 1.6 cm and can beconsumed, while Lettuce plant in medium B grows with an average plant height increase of 0.42 cm and experiencing crop failure, with leaves withered, thus Lettuce on media A managed to grow well, while Lettuce on media B died on the 19th day, so that research with controlling device better than conventional planting.Â Keywords- aeroponic, Atmega328 microcontroller, Arduino Uno R3, Lettuce, Lactuca sativa L